T-Fuzzy Subhypernear-Modules - Onar, Serkan; Ersoy, Bayram Ali; Hila, Kostaq; Davvaz, Bijan (TSINGHUA UNIV PRESS, 2023)
The objective of this study is to investigate the fuzzy subhypernear-modules over hypernear-ring by using a triangular norm, which is T-fuzzy subhypernear-modules are a generalization of fuzzy submodules of hyper near-modules, and some related properties are discussed. Idempotent T-fuzzy subhypernear-module of hypernear-module and subhypernear-module of hypernear-module are suggested. The relation between a level subset of T-fuzzy subhypernear-module of hypernear-module and subhypernear-modules are presented. Also, the image and inverse image of T-fuzzy subhypernear-modules under a mapping are introduced. The direct product of T-fuzzy subhypernear-modules are investigated and the finite direct product of hypernear-modules are characterized in terms of T-fuzzy subhypernear-modules.
Keywords: hypernear-module; t -norm; fuzzy subhypernear-module; T -fuzzy subhypernear-module; HYPERIDEALS; Mathematics